Methodological Approaches to Assessing the Participation of National Economies in Global Value Chains - I. G. Rromanov (Управленческое консультирование, 2025)
The article examines the conceptual basis of international fragmentation of production in the form of global value chains (GVCs) as an important feature of globalization of the world economy. The aim of the study is to reveal the key methodological approaches that allow measuring the participation of national economies in GVCs. Traditional international trade statistics published on the oﬃcial websites of state customs authorities are not suﬃcient to address this task. The concept of trade in value added suggested by the Organization for Economic Cooperation and Development (OECD) in the early 2010s is analyzed, the main indicators of countries’ integration into GVCs are identiﬁed and systematized, as well as the leading international databases on GVCs are described with their strengths and drawbacks being shown. The author concludes that the existing methodological approaches to the investigation of GVCs provide new insight into the positioning of countries and regions in global production and trade. The relevant statistics can be applied both by transnational corporations to optimize the geography of their GVCs and improve the eﬃciency of their activities, and by host countries’ governments implementing the strategies of economic development.